Connectomic mapping of brain-spinal cord neural networks: Future directions in assessing spinal cord injury at rest. (March 2022) - Zhang, Lijian; Wang, Luxuan; Xia, Hechun; Tan, Yanli; Li, Chunhui; Fang, Chuan
Highlights: Neural plasticity occurs at multi-level of the central nervous system following spinal cord injury. Advanced neuroimaging methods are useful for connectomic analysis along the brain-spinal cord axis. Connectomic analysis of brain-spinal cord network provide novel insights into the pathologies of spinal cord injury. Abstract: Following spinal cord injury (SCI), the central nervous system undergoes significant reconstruction. The dynamic change in the interaction of the brain-spinal cord axis as well as in structure-function relations plays a vital role in the determination of neurological functions, which might have important clinical implications for the treatment and its efficacy evaluation of patients with SCI. Brain connectomes based on neuroimaging data is a relatively new field of research that maps the brain's large-scale structural and functional networks at rest. Importantly, increasing evidence shows that such resting-state signals can also be seen in the spinal cord. In the present review, we focus on the reconstruction of multi-level neural circuits after SCI. We also describe how the connectome concept could further our understanding of neuroplasticity after SCI. We propose that mapping the cortical-subcortical-spinal cord networks can provide novel insights into the pathologies of SCI.